Tindak Pidana Perjudian Dalam Tinjauan Hukum Pidana (Studi Kasus Putusan Nomor 491/Pid.B/PN Mdn Tahun 2017) - Rio Pambudi; Aulia Rosa Nasution; Muazzul Muazzul (Universitas Medan Area, 2020)
Gambling is basically a game where there are parties who bet each other to choose one choice among several choices where only one choice is correct and being a winner means that the player who loses the bet will give the bet to the winner. Gambling rules and bets are determined and agreed before the match starts. Talking about